Discussion on the Comprehensive Influence of E-commerce on Business Administration - Fan, Yang (Asia Pacific Economic and Management Review, 2024)
E-commerce is profoundly changing the traditional business model. Through the seamless connection between online and offline, it has greatly promoted the connectivity of the global sales market, so that enterprises can cross the regional boundaries to achieve more convenient and efficient global operation. At the same time, the multi-channel sales strategy provided by e-commerce not only enriches the choices of consumers, but also helps enterprises to reduce their operating costs and break the geographical restrictions. This paper aims to deeply analyze the impact of e-commerce on the field of business administration, and explore innovative strategies to help enterprises to achieve efficient and flexible development in the complex and changeable market environment.